Antihyperglycemic Potential of Dried Powder Combination of Hygrophila auriculata and Cordia macleodii: In Vivo Study in Sprague Dawley Rats - Farooq M. Almutairi (Journal of Pharmacy and Bioallied Sciences)
Introduction: Hygrophila auriculata (Acanthaceae family) and Cordia macleodii (Boraginaceae family) are two famous Indian plants that had until been unrecognized for their antihyperglycemic effects. This study examined the antihyperglycemic effect of metformin in a rat model of diabetes caused by the alloxan method for dried flower powder of H. auriculata and C. macleodii, both alone and in combination. Materials and Methods: Rat weights ranged from 150-200 g, housed under controlled conditions (25-26°C, 50-55% humidity, 12-hour light/dark cycle) with standard diet and water access. Fresh flowers of H. auriculata and C. macleodii were collected, dried, and powdered. The powders were macerated in methanol, evaporated, and further processed. Acute toxicity was assessed by administering flower powder to rats in doses from 5 mg/kg to 5,000 mg/kg, determining LD50 values per OECD guidelines. Anti-hyperglycemic effects were tested in alloxan-induced diabetic rats, with blood glucose levels measured at intervals after oral administration of the flower powders. The hypoglycemic potential was evaluated using the area under the curve (AUC) method. Results: Five hours after oral treatment, the investigation showed that a mixture of dried flower powder of H. auriculata and C. macleodii significantly reduced blood sugar levels. A key role in modulating the pharmacological action is played by the components derived from plants, including alkaloids and flavonoids. Conclusion: This study will provide light on new avenues for research into the therapeutic treatment of diabetes mellitus via the development of innovative herbal formulations.